Hollow Zeolite Single Crystals: Synthesis Routes and Functionalization Methods. Issue 12 (19th September 2018) - Tuel, Alain; Farrusseng, David
Abstract: Hollow zeolite single crystals represent a new class of materials that have received considerable attention over the last decade. Besides facilitating the transport of molecules in zeolite crystals, the cavity present in hollow crystals offers many possibilities for encapsulating active species and constitutes a closed space that can be used as a nanoreactor. However, despite the simplicity of the concept, the synthesis of hollow zeolites is difficult, as it necessitates to control the chemistry and the spatial distribution of elements throughout the crystals. Here, the different strategies that can be used to transform bulk zeolite crystals into hollow analogs are reported. In particular, selective dissolution as well as dissolution–recrystallization methods are discussed in detail in the case of zeolites with mobile five (MFI) framework type. More sophisticated fabrication strategies are also described for two other major zeolites, namely, zeolites Beta and Y. Additionally, methods to introduce metal nanoparticles with controlled size and composition in the cavity are also addressed. The review ends with concluding remarks, including major challenges and future outlooks in the field. Abstract : Hollow zeolite single crystals have recently emerged as a new class of advanced material with high potential as hosts for the encapsulation of nanoparticles. Recent advances in the methodologies used to transform standard bulk zeolite crystals into their hollow analogs are reviewed. Techniques for the encapsulation of nanoparticles with controlled size and composition into hollow zeolite crystals are also reported.